Delayed COVID respiratory failure: what every front line healthcare worker needs to know - Hedges Mary S.; Jackson Kensler D.; Matcha Gautam V.; Ramakrishna Jahanavi M.; Libertin Claudia R. (Sciendo, 2020)
The pandemic of COVID-19 has presented several diagnostic challenges in both recognition of acute disease and also the temporal presentation of disease convalescence with return to normal activity. We present a case of delayed clinical progression of COVID-19 associated respiratory failure on day 25 after initial symptom onset and, notably, after initial full resolution of symptoms and negative RT-PCR nasopharyngeal testing. The patient's delayed presentation of exertional dyspnea and the utilization of specific characteristics of chest radiography in confirmation with laboratory cytokine measurement allowed for clinical re-categorization of the patient's status to active COVID-19 clinical disease and changed acute management. COVID-19 positive patients should be advised to continue to monitor for respiratory deterioration for a greatly extended period of time, even if RT-PCR testing is negative and initial clinical symptoms have resolved. Frontline healthcare workers, including first responders and primary care providers, also need to be aware to monitor for and recognize this delayed presentation.